The Effect of Company Size, Sales Growth, Profitability and Leverage on Stock Returns in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period: Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan, Profitabilitas dan Leverage Terhadap Return Saham pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Nurul Ajizah; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the effect of firm size, sales growth, profitability and leverage on stock returns in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sampling method used is purposive sampling method. The number of companies sampled in this study are 11 Food And Beverage companies listed on the IDX in the 2015-2019 period. The data used is secondary data. The data analysis method used in this study is Eviews 9. The results of this study indicate that there is an effect of company size on stock returns in Manufacturing companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. There is an effect of Sales Growth (Growth) on Stock Returns in Food and Beverage Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Profitability affects stock returns in Food and Beverage Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Leverage has an effect on Stock Returns in Food and Beverage Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period.